TINDAK TUTUR ILOKUSI DALAM PEMENTASAN DRAMA BERJUDUL MALAM JAHANAM OLEH MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS MUHAMMADIYAH PRINGSEWU - Khoirotunnisa, Amida; Fitriati, Siti; Fitriani, Dwi (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
Language is a tool used to communicate, oral communication involves speakers and speech partners. A speaker is someone who speaks while a speaker is an interlocutor. In pragmatics, speech between speakers and speech partners is known as the term speech act. There are three types of speech acts, namely locution, collusion and collusion. The purpose of this study was to determine and describe illocutionary speech acts in a play entitled Malam Jahanam by students of Indonesian Language and Literature Education, University of Muhammadiyah Pringsewu. The study obtained eight data with details of seven assertive illocutionary speech acts and one commissive speech act.